2016
DOI: 10.1016/j.ijsolstr.2015.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lüders-like bands on NiTi fatigue behaviors

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…It is important to distinguish between cycling in the elastic region, where the material is always austenitic, and in the plateau, where the martensitic transformation occurs. As demonstrated by Zheng et al [46,47], the failure in superelastic Ni-Ti strips always occurs in the part of the sample where the martensitic transformation with Lüders-like bands occurs.…”
Section: Overview Of Sma Fatigue Behaviour From An Elastocaloric Persmentioning
confidence: 81%
“…It is important to distinguish between cycling in the elastic region, where the material is always austenitic, and in the plateau, where the martensitic transformation occurs. As demonstrated by Zheng et al [46,47], the failure in superelastic Ni-Ti strips always occurs in the part of the sample where the martensitic transformation with Lüders-like bands occurs.…”
Section: Overview Of Sma Fatigue Behaviour From An Elastocaloric Persmentioning
confidence: 81%
“…The literature on fatigue tests has suggested that during unloading, the formation of stable remnant B19′ variants, along with de-twinning, grain reorientation effects and the retention of lattice defects within B2 and remnant B19′ grains hinder the latter phase′s reverse transformation back to B2 [14,15,[22][23][24][25][26][27][28]. The combined effect of the above mechanisms serves to increase the magnitude of residual strains upon unloading after each cycle along with a progressive degradation in superelasticity.…”
Section: Stress Increases and Residual Strain Upon Unloadingmentioning
confidence: 99%
“…Fatigue testing of NiTi alloys typically involves repeated cycles of loading up to the end of the macroscopic stress plateau region and then unloading back to zero load. Such investigations reported increases in the irreversible strain component (through highly accumulated dislocation densities and the formation of stable martensite variants with successive cycles) contributing to an increase in the residual strain upon unloading and a progressive degradation in superelasticity involving the retention of an increasing phase fraction of B19′ [14,15,[22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The simulations are based on a SMA behavior in uniaxial tension considering three internal variables: wire temperature T , strain SMA and martensite volume fraction z . Phase changes in NiTi-based SMA wires are generally associated with the propagation of transformation fronts separating austenite and martensite [37][38][39][40], which leads to complex thermomechanical couplings in the case of heterogeneous temperature distribution. For the sake of simplicity, the three variables T , SMA and z were here considered as homogeneous within the wires.…”
Section: Bases Of the Modelmentioning
confidence: 99%